MKSP Scheme: An Effective Approach for Uplifting ’Kudumbashree’ Farm Women in Kerala - V K, Rashida; M J, Mercykutty (Journal of Extension Education, 2021)
A study was conducted to assess the perceived effectiveness of Mahila Kisan Sashaktikaran Pariyojana (MKSP), a women empowerment scheme, in Thrissur district of Kerala. The beneficiary farm women of the scheme were cultivating vegetables and banana mostly on leased land under the supervision of Kerala State Poverty Eradication Mission (Kudumbasree mission). Dimensions of effectiveness were categorized in terms of socio economic development, agricultural input supply, institutional support, knowledge and capacity building and empowerment perspective. The respondents included farm women, mission coordinators and facilitators. Majority of banana farmers mission coordinators and facilitators perceived the effectiveness as good while majority of vegetable farmers, rated it as excellent. Empowerment perspective and socio economic development were the most effective outcomes of the scheme.